The CO2 flooding: prospect and challenges on Malaysian oil field - Ikhsan, Azman; Kasmungin, Sugiatmo; Idris, Ahmad Kamal (1997)
This paper describes the potential of carbon dioxide flooding for enhanced oil recovery (EOR) for Malaysian oil fields. This paper also presents various problems that need further evaluation before embarking on the CO2 project. The potential oil recovery from CO2 flooding is estimated to be more than 500 million STB. The sources of CO2 gas supply are nearby and plenty from the Malaysian gas field and Natuna gas field. Previous study had shown that Malaysia oil fields are suitable for immiscible and miscible CO2 flooding. This paper has identified some of the problems that need more studies to optimize the oil recovery and to provide relevant facilities for injection and processing purposes. Another problem that needs due attention is the economics of this project. As a start, a preliminary study on MMP of CO2 – Malaysian crude was conducted at UTM [Hui, H.L, 1995]. Subsequently, in 1996, a study was initiated to investigate the application of foam for mobility control under CO2 flooding.